2009
DOI: 10.3390/rs1040758
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm for Predicting Phycocyanin Concentrations in Cyanobacteria: A Proximal Hyperspectral Remote Sensing Approach

Abstract: Abstract:The purpose of this research was to evaluate the performance of existing spectral band ratio algorithms and develop a novel algorithm to quantify phycocyanin (PC) in cyanobacteria using hyperspectral remotely-sensed data. We performed four spectroscopic experiments on two different laboratory cultured cyanobacterial species and found that the existing band ratio algorithms are highly sensitive to chlorophylls, making them inaccurate in predicting cyanobacterial abundance in the presence of other chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…Several BG algae have confirmed their apparent high carbon affinities since they could maintain slow net growth even at pH > 10 [7]. Light and nutrient availability are also characteristics which promote CHABs [5]. These facts enhance the importance of monitoring BG algae presence in water supply and recreational reservoirs.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several BG algae have confirmed their apparent high carbon affinities since they could maintain slow net growth even at pH > 10 [7]. Light and nutrient availability are also characteristics which promote CHABs [5]. These facts enhance the importance of monitoring BG algae presence in water supply and recreational reservoirs.…”
Section: Introductionmentioning
confidence: 85%
“…One of the first cases of human fatalities associated with cyanobacteria and their toxins occurred in 1996 at Caruaru, PE, Brazil, where exposure through renal dialysis led to the death of approximately fifty patients [4]. Besides their toxic characteristic, Cyanobacterial Harmful Algal Blooms (CHABs) also degrade aquatic habitats due to their malodorousness [3,5] and the appearance of a scum layer or thick mat on the surface of water.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the estimation of Chl-a is a relatively easy task for Case-1 water, monitoring algal blooms in lakes and coastal water classified as Case-2 waters is a challenging one. The remote sensing reflectance (R) spectra of these water bodies is generally complex because of the presence of many optically active components, such as chlorophylls and carotenoids from phytoplankton and aquatic plants, total suspended solids (TSS), colored dissolved organic matter (CDOM), and sometimes bottom reflectance [16]. Generally, the algorithms developed to detect blooms based on the absorption properties of a single variable absorbing near 700 nm (typical of Chl-a) are inadequate for this type of waters [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ogashawara et al [13] analyzed the performance of several reflectance-based bio-optical models for the estimation of PC. Among the analyzed algorithms, three published band ratios were analyzed: Schalles and Yacobi [14] (R rs (650)/R rs (624)), Simis et al [15] (R rs (709)/R rs (620)) and Mishra et al [16] (R rs (700)/R rs (600)). Results from Ogashawara et al [13] showed that for high concentrations of PC Simis et al [15] and Mishra et al [16] band ratios showed better performance, however for low PC concentrations, locally tuned band ratios have the best performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among the analyzed algorithms, three published band ratios were analyzed: Schalles and Yacobi [14] (R rs (650)/R rs (624)), Simis et al [15] (R rs (709)/R rs (620)) and Mishra et al [16] (R rs (700)/R rs (600)). Results from Ogashawara et al [13] showed that for high concentrations of PC Simis et al [15] and Mishra et al [16] band ratios showed better performance, however for low PC concentrations, locally tuned band ratios have the best performance. This finding enhances Oki's [10] idea of the importance of spectral bands selection for the bio-optical modeling of biogeochemical constituents.…”
Section: Introductionmentioning
confidence: 99%